2019
DOI: 10.1016/s2589-7500(19)30105-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the automated imaging differentiation in parkinsonism (AID-P): a multicentre machine learning study

Abstract: Background Development of valid, non-invasive biomarkers for parkinsonian syndromes is crucially needed. We aimed to assess whether non-invasive diffusion-weighted MRI can distinguish between parkinsonian syndromes using an automated imaging approach. MethodsWe did an international study at 17 MRI centres in Austria, Germany, and the USA. We used diffusion-weighted MRI from 1002 patients and the Movement Disorders Society Unified Parkinson's Disease Rating Scale part III (MDS-UPDRS III) to develop and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 34 publications
4
110
0
Order By: Relevance
“…Improvement in DTI acquisition parameters, especially standardization of the resolution and slice gap, may improve classification performances as suggested previously. 25 In line with previous pathological and imaging studies, the best features for the differentiation between PD and PSP were midbrain and third ventricle volumes 6,7,13,17,28,29 and FA in the SCP. 17,[29][30][31] The putamen volume was highly discriminant between MSA-P and PD, PSP and MSA-C patients in our study, MSA-P being characterized by a prominent putamen atrophy.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Improvement in DTI acquisition parameters, especially standardization of the resolution and slice gap, may improve classification performances as suggested previously. 25 In line with previous pathological and imaging studies, the best features for the differentiation between PD and PSP were midbrain and third ventricle volumes 6,7,13,17,28,29 and FA in the SCP. 17,[29][30][31] The putamen volume was highly discriminant between MSA-P and PD, PSP and MSA-C patients in our study, MSA-P being characterized by a prominent putamen atrophy.…”
Section: Discussionsupporting
confidence: 82%
“…Future work could involve calculating free-water and free-water-corrected measurements in clinical protocols for improved classification accuracy. 25 In conclusion, our study showed that an automated categorization of parkinsonian syndromes was applicable to patients with early to moderately advanced parkinsonism recruited in a clinical environment, despite the variability in scanners and acquisition parameters, volumetry being a robust discriminative biomarker. Medical centers could benefit from such an approach in order to increase diagnostic accuracy and patient management.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations